2004
DOI: 10.1111/j.1365-2249.2005.02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower expression of Th1-related cytokines and inducible nitric oxide synthase in mice with streptozotocin-induced diabetes mellitus infected withMycobacterium tuberculosis

Abstract: SummaryDiabetes mellitus is an important predisposing factor for tuberculosis. The aim of this study was to investigate the mechanism underlying this association using a murine model. Mice with streptozotocin-induced diabetes mellitus were prone to Mycobacterium tuberculosis infection, as indicated by increased numbers of live bacteria in lung, liver and spleen. In diabetic mice, the levels of IL-12 and IFN-g g g g in the lung, liver and spleen were lower than those in control animals on day 14 postinfection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 39 publications
4
79
2
Order By: Relevance
“…This situation provides an opportunity for the yeast to grow and produce infectious foci in liver. Yamashiro et al (36) reported that in diabetic mice, the levels of IL-12 and IFN-gamma in liver were lower than those in control animals on day 14 post-infection, while the opposite was true for IL-4 levels. Treatment of normal and diabetic rats with garlic extract after Candida inoculation caused a considerable inhibitory effect on the growth of the organism in both liver and kidneys.…”
Section: Anti-candidial Effect Of Garlic Extractmentioning
confidence: 96%
“…This situation provides an opportunity for the yeast to grow and produce infectious foci in liver. Yamashiro et al (36) reported that in diabetic mice, the levels of IL-12 and IFN-gamma in liver were lower than those in control animals on day 14 post-infection, while the opposite was true for IL-4 levels. Treatment of normal and diabetic rats with garlic extract after Candida inoculation caused a considerable inhibitory effect on the growth of the organism in both liver and kidneys.…”
Section: Anti-candidial Effect Of Garlic Extractmentioning
confidence: 96%
“…Similarly, metabolic diseases such as diabetes mellitus are known to affect chemotaxis, phagocytosis, activation, and antigen presentation by phagocytes in response to MTB, and this defect does not improve with insulin (Moutschen et al, 1992). Importantly, IFN- production was found to be impared in hyperglycemia (Yamashiro et al, 2005), but another study showed that both IGRA results were not affected in diabetes mellitus patients (Walsh et al, 2011). Intermediate results have been found to be also associated with lower serum albumin and double immunomodulatory therapy (Papay et al,2011).…”
Section: Conditions Altering Igra Resultsmentioning
confidence: 99%
“…In one study they reported Poor glycemic control significantly influences radiographic manifestations of pulmonary TB in patients with DM; isolated lower lung field involvement and large cavities are more common in uncontrolled diabetics than in optimal control patients [24] . The increased frequency of pulmonary cavitary lesions in diabetic patients with poor glycemic control is probably related to reduced expression of Th1-related cytokines [25] . It is possible that proper glycemic control will not only reduce the risk of tuberculosis among diabetes patients but also attenuates the risk of cavitary lesions of pulmonary TB in diabetic patients.…”
Section: Resultsmentioning
confidence: 99%